Anesthetic and Obstetrical Factors Associated With the Effectiveness of Epidural Analgesia for Labor Pain Relief: An Observational Population-Based Study. Issue 1 (1st January 2017) - Bonnet, Marie-Pierre; Prunet, Caroline; Baillard, Christophe; Kpéa, Laure; Blondel, Béatrice; Le Ray, Camille
Abstract : Background and Objectives: The effectiveness of labor epidural analgesia is difficult to explore, as it includes the maternal satisfaction with analgesia as well as the overall childbirth experience. In this population-based study, we sought to identify factors associated with the effectiveness of epidural analgesia for labor pain relief. Methods: We performed a secondary analysis of the 2010 French National Perinatal Survey, a cross-sectional study of a representative sample of births in France. All participants who gave birth with an epidural analgesia were included. Effectiveness of epidural analgesia was assessed 2 to 3 days after delivery and intended to include analgesic efficacy and maternal satisfaction together. The factors analyzed were anesthetic management and maternal, obstetrical, and organizational characteristics, using a logistic regression with random effects model. Results: Among the 9337 women who gave birth with an epidural analgesia and were included, 8377 (89.3%; 95% confidence interval [CI] = 88.7–89.9) considered their epidural to be very or fairly effective. In the multivariate analysis, effectiveness was significantly associated with the use of patient-controlled epidural analgesia (adjusted odds ratio [aOR] = 1.2 [1.0–1.5]; P = 0.02) and delivery in private maternity facilities (aOR = 1.3 [1.1–1.6]); it was significantly less effective in obese women (aOR = 0.6 [0.5–0.8]) and multiparous women not receiving oxytocin during labor (aOR = 0.4 [0.4–0.6]) as compared with nonobese and nulliparous women with oxytocin, respectively. Conclusions: At the population level, most women found epidural analgesia effective for labor pain relief, but specific attention should be paid to obese parturients and multiparous women not receiving oxytocin. High epidural effectiveness with patient-controlled analgesia should promote an increased use of this method.